Pengaruh Suplementasi Cacing Tanah (Lumbricus rubellus) pada Pakan terhadap Produktivitas dan Kualitas Telur Itik - Sukarne Sukarne; Asnawi Asnawi; Anwar Rosyidi (Indonesian, 2020)
The high needs of community for poultry products, especially duck eggs must be balanced with the availability of quality feed. Good feed will be positively correlated with increased productivity and product quality. This study aims to evaluate the effect of earthworm supplementation to duck feed on increasing production and quality of duck eggs. The research material used was ducks aged 6 months as many as 60 heads which were divided into 2 treatments and 5 replications, each replication containing 6 female local ducks. Feed treatment was divided into 2, basal feed (rice bran 70% + corn 30%) and treatment feed (basal feed + 20% fresh earthworms). The results of this study showed a significant difference in egg production (12 ± 1.58 eggs and 20 ± 3.87 eggs) (P> 0.05) but not significantly different in egg weight (61.9 ± 6.58 and 60.4 ± 6.06), egg length and egg width (60.06 ± 2.05 and 53.81 ± 9.64). The results of experiments on egg resistance against several pathogenic bacteria showed that there was an increase in inhibitory power against Salmonella typhy, Escherichia coli, Bacillus cereus and Staphylococcus aureus on egg white (albumen) of duck eggs which added 20% of worms in the feed.